(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
In the construction industry, 3D concrete printing technology is one of the advancetechnique that can be used for the construction of building components or to print entire buildings.The 3D concrete printing techniques are being foreseen as a solution for solving the housing crisisacross various parts of the world. There are various advantages associated with 3D concreteprinting technology over conventional building methods as well as other advanced techniques suchas its fast construction, cost-effective, minimal wastage, that would lead to the sustainableconstruction process as well as a cost-effective construction method.The goal of the paper is the evaluating the financial feasibility for advance technologies such asMonolithic concrete construction, Precast system 3D concrete printing for the Affordable masshousing in the construction industry which gives the benefit in financial aspect with respect to totime in the construction project. Financial factors are being derived by various case studies of 3Dconcrete printing market rates for the cost of construction, and used in sample case forassessment. The current hypothesis of the dissertation is to use advance 3D concrete printingtechnology as a cost-effective technique for affordable housing. The research concludes with thestudy of technique, SWOT analysis, organizational implementation of the process of the project,advance Construction methods used for affordable housing, Time cost factors attached to it. Theend-stage of the research is about the assessment financial feasibility of the techniques amongstthemselves which can be useful for the construction of affordable housing projects as well as otherprojects.